EFFECT OF LENGTH OF FISH ON THE OCCURRENCE OF HELMINTH PARASITES - SHOMORENDRA, M.; JHA, A. N.; KUMAR, PANKAJ (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
Fishes of different length groups of Channa gachua (Ham), C striatus (Bl.). Clarias batrachus (L.) and -nabas testidineus (Bl.) were examined regularly for parasitic infection between January 2000 to January 2001. One species of digenetic trematode, two species of cestode, one species of nematode and one species of Acanthocephala were collected. The parasite species showed significant variation in the prevalence and intensity of occurrence in different length groups of fish hosts. Such variations shown due to considerable change in diet of fish hosts with the increasing size. Intermediate hosts and choice of food items are also factors of parasite infection.